Antimonoamine Oxidase and Antioxidant Properties of Phenolic Compounds Functionalized with Amine and Carboxyl Groups - Grigoryan, A. S.; Alaverdyan, Zh. R.; Pagutyan, N. A.; Hunanyan, O. A.; Baghdasaryan, S. V.; Navoyan, K. G.; Agekyan, A. A.; Gasparyan, H. V. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The effect of carboxy- and amino-substituted phenolic compounds on the activity of monoamine oxidase (MAO) in bovine brain and on oxidative processes in the brain and liver of rats was studiedin vitro. It has been established that some of the studied compounds exhibit certain anti-MAO and antioxidant properties. An attempt was made to compare the biological properties of the compounds with the activity of known drugs. In the series of aminosubstituted derivatives, 4-(1-amino-2-methylpropan-2-yl) benzene-1,2- diol displaed high antimonoamine oxidase and antioxidant activity. Հետազոտվել է նոր սինթեզված հեքսաբրոմիդների ակտիվությունը մոնոամինօքսիդազա (ՄԱՕ) ֆերմենտի և հակաօքսիդանտների նկատմամբ առնետի ուղեղի և լյարդի վրա in vitro փորձերում: Հաստատվել է, որ որոշ հետազոտվող միացություններ` հիդրոբրոմիդ, հիդրոքսիֆենիլ, 3,4-դիհիդրոքսիցիկլոպենտիլի ածանցյալները ցուցաբերում են որոշակի հակաՄԱՕ և հակաօքսիդանտ ակտիվություն: Փորձ է արվել համեմատելու միացությունների կենսաբանական ակտիվությունը հայտնի միացությունների հակաՄԱՕ և հակաօքսիդանտ ակտիվությունների հետ: Изучено влияние карбокси и аминозамещенных фенольных соединений на активность моноаминоксидазы (МАО) в мозгу крупного рогатого скота и на окислительные процессы в мозгу и печени крыс in vitro. Установлено, что некоторые из изученных соединений проявляют определенные антиМАО и антиоксидантные свойства. Была предпринята попытка сравнить биологические свойства соединений с активностью известных препаратов. В ряду аминозамещенных производных 4-(1-амино-2-метил- пропан-2-ил)бензол-1,2-диол обладает высокой антимоноаминоксидазной и антиоксидантной активностью.
Keywords: Pharmacology